Understanding the Mechanisms of Resistance to CAR T-Cell Therapy in Malignancies - Cheng, Jiali; Zhao, Lei; Zhang, Yuanyuan; Qin, Yun; Guan, Yuqi; Zhang, Tong; Liu, Chaohong; Zhou, Jianfeng (Frontiers in Oncology, 2019)
Taking advantage of the immune system to exert an antitumor effect is currently a novel approach in cancer therapy. Adoptive transfer of T cells engineered to express chimeric antigen receptors (CARs) targeting a desired antigen has shown extraordinary antitumor activity, especially in refractory and relapsed B-cell malignancies. The most representative in this respect, as well as the most successful example, is CD19 CAR T-cell therapy in B-cell acute lymphoblastic leukemia (B-ALL). However, with the widespread use of CAR T-cell therapy, the problems of resistance and relapse are being gradually considered. This review provides a comprehensive picture of the mechanisms of resistance to CAR T-cell therapy from three aspects, namely, CAR T-cell factors, tumor factors and tumor microenvironment factors, offering insights to improve CAR T-cell therapy.